Facile sonochemical synthesis of N,Cl-codoped TiO2: Synthesis effects, mechanism and photocatalytic performance - Teh, C.Y.; Wu, T.Y.; Juan, J.C. (Elsevier, 2015)
In this study, both nitrogen and chlorine were successfully doped into TiO2(N,Cl-codoped TiO2) via a sonochemical method using titanium(IV) butoxide and ammonium chloride as precursors. When N,Cl-codoped TiO2was tested on the decolorization of CI Reactive Black 5 (RB5), it was observed that the photocatalytic activity exhibited by the synthesized photocatalyst was greatly affected by the synthesis conditions. Increasing the sonication intensity or duration up to a certain point shifted the absorption onset toward a lower energy and improved the crystallinity of the synthesized photocatalyst. It was also observed that increasing the N,Cl:Ti molar ratio to 2 significantly enhanced the photocatalytic activity of N,Cl-codoped TiO2, but higher molar ratios inhibited the decolorization of RB5. A relatively low calcination temperature of 200°C was sufficient to further improve the photocatalytic activity of N,Cl-codoped TiO2. The following recommended synthesis conditions successfully yielded 96.02% RB5 decolorization under visible light irradiation for 5h: sonication amplitude of 40%, sonication duration of 3.62h, N,Cl:Ti molar ratio of 2 and calcination temperature of 200°C. The decolorization rate constant of N,Cl-codoped TiO2(0.01min-1) was also significantly higher than that of commercially available P25 (0.0055min-1).